Development of deterioration curves for flexible pavement and uncertainty factor - Picado Muñoz, Greivin (2025)
Due to planning issues in the Local Road Network of Costa Rica, an important amount of roads have an advanced level of distress and receive inappropriate maintenance activities, which implies a high cost for local governments. This is because several of the Road Management Units do not have the studies and basic information needed to generate the deterioration curves that would allow to identify the state of the roads. The following project seeks to make an assessment of the roads in the Metropolitan Area, in the provinces of San José, Alajuela, Cartago and Heredia; in order to recognize the roads’ condition and develop the deterioration curves from the information collected in field. The ASTM D-6433 Standard was applied for the field condition survey of the distress and the calculating of the Pavement Condition Index. Next, the deterioration curves where created by using a multivariate statistical analysis of the data obtained. Having found the deterioration curves and the equation that includes the uncertainty factor, an useful tool is obtained, which can generate a deterioration model of the roads, allowing the department in charge to establish the optimal timing of pavement preventive maintenance, the adequate maintenance activities according to the level of distress and a proper distribution of the public resources.